About medicalization: Origin, causes and consequences part I - La Valle, Ricardo (Revista del Hospital Italiano de Buenos Aires, 2014)
Medicalization is the social process that aims to turn situations usually considered as normal into pathological conditions, and to resolve through medicine situations that are not strictly medical but social, professional or of personal relationships. Disease mongering is expanding the boundaries of what is considered as disease, in order to increase the markets for those who sell and provide treatments. The process of medicalization, according to Foucault, began in the eighteenth century with the establishment of the first modern state, Prussia, and the emergence of Medicine of the State, which is not the result of private medicine but a social medicine. In the late twentieth century social changes that influence the process of medicalization occur: the Industrial Revolution, the growth of cities, urbanization of the population, economic liberalism, World Wars, et cetera. During the Industrial Revolution, the chemical industry developed, which in turn led to pharmaceutical development, which served as the scientific complement for medicine during the eighteenth century. In the twentieth century, medicine acquires the ability to cause death as the result of its own activity –"positive iatrogenia"— and moves toward the nonsick man arrogating a normalizing power. During the second half of the twentieth century, the fall of the Bretton Woods Agreement, neoliberalism and postmodernism enable the transformation of medicine into a market object which, together with Flexnerian medical education, results the perfect breeding ground for this process and paves the road to indefinite medicalization with the petty objective of maximizing an obscene profit from medicine as a commodity